1998
DOI: 10.1111/j.2042-3306.1998.tb04515.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytology of 100 samples of abdominal fluid from 100 horses with abdominal disease

Abstract: Summary A total of 100 samples of abdominal fluid (AF) from 100 horses with abdominal disease were evaluated by cytology. Cytology results were subsequently correlated with the final outcome of the disease. The horses were classified into 4 groups: Group I, horses that were treated with conventional (nonsurgical) therapy and recovered; Group II, horses that had surgery and survived; Group III, horses that had surgery but died; and Group IV, horses that were subjected to euthanasia prior to surgery. Statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 11 publications
1
20
0
1
Order By: Relevance
“…Moreover, the occurrence of total protein concentrations under the standard reference value of 2.5g/dL even with intestinal ischemia reported here support previous studies that suggested a maximum reference value of 1.5g/dL (Browlow et al 1981, Garma-Aviña 1998. Some authors consider that 2.5g/dL should be used, considering the difficulty in obtaining accurate values lower than this with the refractometer, which is the most widely used method (DeHeer et al 2002).…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, the occurrence of total protein concentrations under the standard reference value of 2.5g/dL even with intestinal ischemia reported here support previous studies that suggested a maximum reference value of 1.5g/dL (Browlow et al 1981, Garma-Aviña 1998. Some authors consider that 2.5g/dL should be used, considering the difficulty in obtaining accurate values lower than this with the refractometer, which is the most widely used method (DeHeer et al 2002).…”
Section: Discussionsupporting
confidence: 74%
“…Red granules are also known to appear occasionally in the cytoplasm of mesothelial cells of the abdominal fluid, and cases in horses have been documented. 6 More studies are necessary to accurately establish the relative frequency of the various cell types found in animals and humans. Also, a topographical cytological study on the choroid plexi would be useful to pinpoint the precise spatial location of these cells within the choroid plexi, as well as to determine whether all the ventricles share the same cytological composition.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the sediment smear along with the protein levels and PCV can characterize the disease process. [38][39][40][41][42][43][44][45][46] The PP (total solids) should be used to determine the pathogenesis of the fluid development. Fluids with low protein levels (less than 1.5 g/dL) are considered pure transudates; this implies that water has leaked from vessels as a result of altered fluid forces, including hydrostatic and oncotic pressures.…”
Section: Fluid Evaluationmentioning
confidence: 99%